AI Paraphrasing Tools in EFL Undergraduate Thesis Writing: Students' Perceptions and Influential Factors - Pratami, Silvia; Eryansyah; Vianty, Machdalena (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2025)
English as a Foreign Language (EFL) students often struggle with academic writing, especially when working on undergraduate theses. This study explores the perceptions and factors influencing using AI-based paraphrasing tools by English as a Foreign Language (EFL) undergraduate students in their thesis writing. The study used a qualitative descriptive method and a case study design involving 53 students. The data collection method used a questionnaire and semi-structured interviews with five participants from the 9th semester of the English education study program. Data collection instruments used questionnaires and interviews. The data analysis technique used qualitative descriptive analysis. The study results showed that students considered AI-based paraphrasing tools helpful in saving time, improving vocabulary, and avoiding plagiarism. The main factors influencing their use included time management, institutional requirements for originality, and the desire to improve the quality of writing. Despite positive perceptions, students also expressed concerns about over-reliance on the tools and the potential for decreased originality. The study concluded that although AI-based paraphrasing tools support academic writing, they should be a complement, not a substitute, for critical writing skills.